3-(3-Methoxybenzylidene)chroman-4-one - Gopaul, Kaalin (International Union of Crystallography, 2012)
In the title compound, C(17)H(14)O(3), the dihedral angle between the methoxybenzene unit and the benzene ring of the chromanone system is 64.12 (3)°. The crystal structure is stabilized by weak C—H⋯O interactions.